Posttranslational regulation of polycystin‐2 protein expression as a novel mechanism of cholangiocyte reaction and repair from biliary damage. Issue 6 (10th October 2015) - Spirli, Carlo; Villani, Ambra; Mariotti, Valeria; Fabris, Luca; Fiorotto, Romina; Strazzabosco, Mario
Abstract : Polycystin‐2 (PC2 or TRPPC2), a member of the transient receptor potential channel family, is a nonselective calcium channel. Mutations in PC2 are associated with polycystic liver diseases. PC2‐defective cholangiocytes show increased production of cyclic adenosine monophosphate, protein kinase A–dependent activation of the extracellular signal–regulated kinase 1/2 (ERK1/2) pathway, hypoxia‐inducible factor 1α (HIF‐1α)–mediated vascular endothelial growth factor (VEGF) production, and stimulation of cyst growth and progression. Activation of the ERK/HIF‐1α/VEGF pathway in cholangiocytes plays a key role during repair from biliary damage. We hypothesized that PC2 levels are modulated during biliary damage/repair, resulting in activation of the ERK/HIF‐1α/VEGF pathway. PC2 protein expression, but not its gene expression, was significantly reduced in mouse livers with biliary damage (Mdr2 –/– knockout, bile duct ligation, 3, 5‐diethoxycarbonyl‐1, 4‐dihydrocollidine treatment). Treatment of cholangiocytes with proinflammatory cytokines, nitric oxide donors, and endoplasmic reticulum stressors increased ERK1/2 phosphorylation, HIF‐1α transcriptional activity, secretion of VEGF, and VEGF receptor type 2 phosphorylation and down‐regulated PC2 protein expression without affecting PC2 gene expression. Expression of homocysteine‐responsive endoplasmic reticulum–resident ubiquitin‐like domain member 1 protein and NEK, ubiquitin‐like proteins that promote proteosomal PC2 degradation, was increased. Pretreatment with the proteasome inhibitor MG‐132 restored the expression of PC2 in cells treated with cytokines but not in cells treated with nitric oxide donors or with endoplasmic reticulum stressors. In these conditions, PC2 degradation was instead inhibited by interfering with the autophagy pathway. Treatment of 3, 5‐diethoxycarbonyl‐1, 4‐dihydrocollidine mice and of Mdr2 –/– mice with the proteasome inhibitor bortezomib restored PC2 expression and significantly reduced the ductular reaction, fibrosis, and phosphorylated ERK1/2. Conclusion : In response to biliary damage, PC2 expression is modulated posttranslationally by the proteasome or the autophagy pathway, and PC2 down‐regulation is associated with activation of ERK1/2 and an increase of HIF‐1α‐mediated VEGF secretion; treatments able to restore PC2 expression and to reduce ductular reaction and fibrosis may represent a new therapeutic approach in biliary diseases.(Hepatology 2015;62:1828–1839)